2016
DOI: 10.1016/j.jtusci.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and thermoluminescence glow curve study of gadolinium-doped Y2O3nanophosphor

Abstract: Gadolinium-doped Y 2 O 3 nanophosphor was synthesized by a solid-state reaction method, which could be used for large-scale production of phosphors. The structure of the phosphor sample was characterized by powder X-ray diffraction, field emission gun scanning electron microscopy and high-resolution transmission electron microscopy. The particle size was calculated from Scherer's formula. X-ray diffraction showed a grain size of 35-55 nm, in good agreement with the scanning electron microscopy image. The synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The electrons that transitioned from the conduction band were either re-trapped at the trap level or defect centre or at the hole trap or luminescence centre, where they recombine with holes, giving rise to luminescence or the glow peak. Trapped charge carriers are found inside the forbidden band gap, as confirmed by the calculated trap parameters [19,20].…”
Section: Discussion and Model For Uv-irradiated Phosphorsupporting
confidence: 65%
“…The electrons that transitioned from the conduction band were either re-trapped at the trap level or defect centre or at the hole trap or luminescence centre, where they recombine with holes, giving rise to luminescence or the glow peak. Trapped charge carriers are found inside the forbidden band gap, as confirmed by the calculated trap parameters [19,20].…”
Section: Discussion and Model For Uv-irradiated Phosphorsupporting
confidence: 65%
“…RE-doped yttria nanopowders have been synthesized by several methods, such as hydrolysis, combustion, high-temperature solid-state reactions, sol-gel, precipitation, molten salt, solvothermal, hydrothermal, etc. In almost all the mentioned methods of producing yttrium oxide with or without RE-dopants, due to the amorphous nature of as-prepared samples, high-temperature crystallization reaches up to 1700 °C to obtain a highly crystalline state, which directly leads to an increase in the average particle size [ [1] , [2] , [3] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Of course, Chen et al reported the production of yttria in micron dimensions at a temperature of 600 °C [ 20 ].…”
Section: Introductionmentioning
confidence: 99%